George Soros: The Prophet and the Loss
Two part documentary about George Soros exploring his life, businesses and philanthropic activities, as well as his business philosophy. The film contains interviews with Richard Medley (Former Quantum Fund Manager), Crispin Odey (Odey Asset Management Ltd.) and Jeremy Hawkins (Bank of America) who recall the “Black Wednesday” (September 16, 1992), the day when Soros shocked the world by earning an estimated US$ 1.1 billion from speculations concerning the Bank of England and the sterling. Next, the film looks for clues to understand how George Soros’s financial and philanthropic side developed and functioned together. The film starts with his early years in Budapest when he was a child hiding from the German troops. Then, Gary Gladstein (Managing Director, Quantum Fund), Simon Kester and Nora Degara talk about his early years as an adolescent in London. Alan Cohn (Wertheim Schroeder & Co) and Susan Soros (George Soros’ wife) describe his life in New York. George Soros himself talks about the need to give away the money and how the Quantum Fund was set for distributing funds all over the world. Cristina Kruck (Soros Roma Foundation), Anna Csongor (Csenyeta School Project) and Zsolt Csalog (Writer) speak about George Soros’ philanthropy. The film ends with George Soros describing his choices and his approach to life, which in the end provides a more detailed portrait of both the financier and the philanthropist.